2020
DOI: 10.1111/ppe.12683
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hypertensive disorders and subtypes of hypospadias: A Dutch case‐control study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Sherrif et al observed notable positive associations between hypertension and hypospadias (OR 1.68; 95% CI 1.46–1.93) (Sheriff et al, 2019). However, a study by Jamaladin et al found no associations between maternal hypertensive disorders in general, chronic hypertension, or gestational hypertension and hypospadias or its subtypes (Jamaladin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sherrif et al observed notable positive associations between hypertension and hypospadias (OR 1.68; 95% CI 1.46–1.93) (Sheriff et al, 2019). However, a study by Jamaladin et al found no associations between maternal hypertensive disorders in general, chronic hypertension, or gestational hypertension and hypospadias or its subtypes (Jamaladin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%